A new species of planthopper in the genus Kubilaya (Hemiptera: Auchenorrhyncha: Derbidae) from oil palms (Elaeis guineensis) in Colombia, a key to the genus, and an updated molecular phylogeny of the New World Otiocerinae - Guerrero, Miriam Rosero; Rodríguez, Anuar Morales; Bartlett, Charles R.; Bahder, Brian W. (Zootaxa, 2026)
During a recent survey of oil palms in Colombia to document planthopper diversity and search for putative vectors of the causal agent of Lethal Wilt, a new species of planthopper in the genus Kubilaya (Derbidae) was discovered. Herein, the novel taxon is described along with supplemental molecular data for the barcoding region (5’ half) of the cytochrome c oxidase subunit I (COI) gene, 18S rRNA gene and D8–D10 expansion regions of the 28S rRNA gene are provided. An updated molecular phylogeny of the New World Otiocerinae and a key to species of the genus Kubilaya are provided.